An agonist of the CXCR4 receptor accelerates the recovery from the peripheral neuroparalysis induced by Taipan snake envenomation. - Marco Stazi; Giorgia D'Este; Andrea Mattarei; Samuele Negro; Florigio Lista; Michela Rigoni; Aram Megighian; Cesare Montecucco (Public Library of Science (PLoS), 2020)
Envenomation by snakes is a major neglected human disease. Hospitalization and use of animal-derived antivenom are the primary therapeutic supports currently available. There is consensus that additional, not expensive, treatments that can be delivered even long after the snake bite are needed. We recently showed that the drug dubbed NUCC-390 shortens the time of recovery from the neuroparalysis caused by traumatic or toxic degeneration of peripheral motor neurons. These syndromes are characterized by the activation of a pro-regenerative molecular axis, consisting of the CXCR4 receptor expressed at the damaged site in neuronal axons and by the release of its ligand CXCL12α, produced by surrounding Schwann cells. This intercellular signaling axis promotes axonal growth and functional recovery from paralysis. NUCC-390 is an agonist of CXCR4 acting similarly to CXCL12α. Here, we have tested its efficacy in a murine model of neuroparalytic envenoming by a Papuan Taipan (Oxyuranus scutellatus) where a degeneration of the motor axon terminals caused by the presynaptic PLA2 toxin Taipoxin, contained in the venom, occurs. Using imaging of the neuromuscular junction and electrophysiological analysis, we found that NUCC-390 administration after injection of either the purified neuroparalytic Taipoxin or the whole Taipan venom, significantly accelerates the recovery from paralysis. These results indicate that NUCC-390, which is non-toxic in mice, should be considered for trials in humans to test its efficacy in accelerating the recovery from the peripheral neuroparalysis induced by Taipans. NUCC-390 should be tested as well in the envenomation by other snakes that cause neuroparalytic syndromes in humans. NUCC-390 could become an additional treatment, common to many snake envenomings, that can be delivered after the bite to reduce death by respiratory deficits and to shorten and improve functional recovery.